Respuesta :
-10.
Solution: Multiply the negative three fourths by everything in the parenthesis.
[tex] - \frac{3}{4} x + ( - \frac{3}{2} ) = 6[/tex]
Add the negative three halves to both sides.
[tex] - \frac{3}{4} x = \frac{15}{2} [/tex]
Multiply both sides by negative four thirds.
[tex]x = - 10[/tex]
[tex]\bold{Answer}[/tex]
[tex]\boxed{\bold{X \ = \ -10}}[/tex]
[tex]\bold{Explanation}[/tex]
- [tex]\bold{Simplify: \ -\frac{3}{4}\left(x+2\right)=6}[/tex]
[tex]\bold{-------------------}[/tex]
- [tex]\bold{Multiply \ Both \ Sides \ By \ -4}[/tex]
[tex]\bold{\left(-\frac{3}{4}\left(x+2\right)\right)\left(-4\right)=6\left(-4\right)}[/tex]
- [tex]\bold{Simplify}[/tex]
[tex]\bold{3\left(x+2\right)=-24}[/tex]
- [tex]\bold{Divide \ Both \ Sides \ By \ 3}[/tex]
[tex]\bold{\frac{3\left(x+2\right)}{3}=\frac{-24}{3}}[/tex]
- [tex]\bold{Simplify}[/tex]
[tex]\bold{x+2=-8}[/tex]
- [tex]\bold{Subtract \ 2 \ From \ Both \ Sides}[/tex]
[tex]\bold{x+2-2=-8-2}[/tex]
- [tex]\bold{Simplify}[/tex]
[tex]\bold{X \ = \ -10}[/tex]
[tex]\boxed{\bold{Eclipsed}}[/tex]